PERSONALIZATION OF THE CHILD'S PERSONALITY BASED ON COMPLEX TRAINING (Conferencea, 2024)
This article describes the personalization of the child's personality on the basis of complex training, that is, the theoretical foundations and practical experiences that determine the content of the activation of children's self-expression, as well as thoughts and reflections on it.